Monitoring and evaluation practices and project outcome of tech start-ups in Ghana: The moderating role of the Business environment - Ramatu Issifu; Daniel Agyapong (Cogent Business & Management, 2023)
Issues relating to Monitoring and Evaluation (M&E) have been established as a key and fundamental tool for the successful implementation of projects regardless of the industry. The study therefore sought to address the following questions: what effect do monitoring and evaluation practices have on tech start-ups project outcomes, as well as the role that business environment play in the relationship between M&E and project outcomes. The study followed a positivist mind-set, relying only on quantitative methods and an explanatory research design. Primary data via structured questionnaire was obtained from 317 respondents in managerial positions in the tech industry and analysed using inferential and descriptive tools. The study found that monitoring practices had a positive significant effect on project outcome. Evaluation practices also had a positive significant effect on project outcome. Business environment was found to have a dampening significant moderating effect in the relationship between evaluation practices and project outcome. However, business environment did not have any significant effect in the relationship between monitoring practice and project outcome. These findings will enable project practitioners understand the dynamics of monitoring and evaluation and the business environment when it comes to project execution. It will further enable project managers, personnel, and donors recognize how significant M&E tools are when creating policies and managing performance. Moreover, tech start-ups should create policies that recognize the integration of M&E in their operations and business functions.
Keywords: 650; Business Environment; Evaluation Practices; Monitoring Practices; Project Outcome; Tech Start-ups